Optimal. Leaf size=26 \[ \left (2+e^2\right )^2 \left (-3+x+e^{2+x-e^{-x} x} x\right ) \]
________________________________________________________________________________________
Rubi [F] time = 0.72, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int e^{-x} \left (e^x \left (4+4 e^2+e^4\right )+e^{e^{-x} \left (-x+e^x (2+x)\right )} \left (-4 x+4 x^2+e^4 \left (-x+x^2\right )+e^2 \left (-4 x+4 x^2\right )+e^x \left (4+4 x+e^4 (1+x)+e^2 (4+4 x)\right )\right )\right ) \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int e^{-e^{-x} x} \left (2+e^2\right )^2 \left (e^{e^{-x} x}+e^2 (-1+x) x+e^{2+x} (1+x)\right ) \, dx\\ &=\left (2+e^2\right )^2 \int e^{-e^{-x} x} \left (e^{e^{-x} x}+e^2 (-1+x) x+e^{2+x} (1+x)\right ) \, dx\\ &=\left (2+e^2\right )^2 \int \left (1+e^{2-e^{-x} x} (-1+x) x+e^{2+x-e^{-x} x} (1+x)\right ) \, dx\\ &=\left (2+e^2\right )^2 x+\left (2+e^2\right )^2 \int e^{2-e^{-x} x} (-1+x) x \, dx+\left (2+e^2\right )^2 \int e^{2+x-e^{-x} x} (1+x) \, dx\\ &=\left (2+e^2\right )^2 x+\left (2+e^2\right )^2 \int \left (e^{2+x-e^{-x} x}+e^{2+x-e^{-x} x} x\right ) \, dx+\left (2+e^2\right )^2 \int \left (-e^{2-e^{-x} x} x+e^{2-e^{-x} x} x^2\right ) \, dx\\ &=\left (2+e^2\right )^2 x+\left (2+e^2\right )^2 \int e^{2+x-e^{-x} x} \, dx-\left (2+e^2\right )^2 \int e^{2-e^{-x} x} x \, dx+\left (2+e^2\right )^2 \int e^{2+x-e^{-x} x} x \, dx+\left (2+e^2\right )^2 \int e^{2-e^{-x} x} x^2 \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.16, size = 24, normalized size = 0.92 \begin {gather*} \left (2+e^2\right )^2 \left (1+e^{2+x-e^{-x} x}\right ) x \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.96, size = 43, normalized size = 1.65 \begin {gather*} x e^{4} + 4 \, x e^{2} + {\left (x e^{4} + 4 \, x e^{2} + 4 \, x\right )} e^{\left ({\left ({\left (x + 2\right )} e^{x} - x\right )} e^{\left (-x\right )}\right )} + 4 \, x \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [B] time = 0.34, size = 54, normalized size = 2.08 \begin {gather*} x e^{4} + 4 \, x e^{2} + x e^{\left (-x e^{\left (-x\right )} + x + 6\right )} + 4 \, x e^{\left (-x e^{\left (-x\right )} + x + 4\right )} + 4 \, x e^{\left (-x e^{\left (-x\right )} + x + 2\right )} + 4 \, x \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.06, size = 42, normalized size = 1.62
method | result | size |
risch | \(4 \,{\mathrm e}^{2} x +x \,{\mathrm e}^{4}+4 x +\left ({\mathrm e}^{4}+4 \,{\mathrm e}^{2}+4\right ) x \,{\mathrm e}^{\left ({\mathrm e}^{x} x +2 \,{\mathrm e}^{x}-x \right ) {\mathrm e}^{-x}}\) | \(42\) |
norman | \(\left (\left ({\mathrm e}^{4}+4 \,{\mathrm e}^{2}+4\right ) x \,{\mathrm e}^{x}+\left ({\mathrm e}^{4}+4 \,{\mathrm e}^{2}+4\right ) x \,{\mathrm e}^{x} {\mathrm e}^{\left (\left (2+x \right ) {\mathrm e}^{x}-x \right ) {\mathrm e}^{-x}}\right ) {\mathrm e}^{-x}\) | \(51\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [F] time = 0.00, size = 0, normalized size = 0.00 \begin {gather*} x e^{4} + 4 \, x e^{2} + 4 \, x + \int {\left (x^{2} {\left (e^{6} + 4 \, e^{4} + 4 \, e^{2}\right )} - x {\left (e^{6} + 4 \, e^{4} + 4 \, e^{2}\right )} + {\left (x {\left (e^{6} + 4 \, e^{4} + 4 \, e^{2}\right )} + e^{6} + 4 \, e^{4} + 4 \, e^{2}\right )} e^{x}\right )} e^{\left (-x e^{\left (-x\right )}\right )}\,{d x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 0.85, size = 21, normalized size = 0.81 \begin {gather*} x\,\left ({\mathrm {e}}^{x-x\,{\mathrm {e}}^{-x}+2}+1\right )\,{\left ({\mathrm {e}}^2+2\right )}^2 \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.29, size = 39, normalized size = 1.50 \begin {gather*} x \left (4 + 4 e^{2} + e^{4}\right ) + \left (4 x + 4 x e^{2} + x e^{4}\right ) e^{\left (- x + \left (x + 2\right ) e^{x}\right ) e^{- x}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________